Study on the dynamic evolution and synergistic relationship between urbanization and eco-efficiency through the selection of 76 agricultural counties and districts in Liaoning province as research units - Gao, Yanpeng; Guo, Chunyao; Wei, Ye (Frontiers in Ecology and Evolution, 2022)
Coordination and interaction among urbanization processes, efficient resource utilization, and ecological protection have emerged as key challenges for spatial development and protection of a territory. In this paper, we quantitatively determined the urbanization level and eco-efficiency by utilizing the entropy evaluation method and the SBM model with undesirable outputs, and then employed kernel density estimation, center movement method, and bivariate Moran's I index method to examine the spatial-temporal pattern as well as the interaction between the above two factors. This study provides a new framework for the measurement of urbanization and eco-efficiency and their interaction. The results of the study in the research area demonstrate that: (1) From 2013 to 2017, the urbanization level exhibited a steady increase from 0.2468 to 0.2789, while eco-efficiency depicted an N-shaped development trend before suffering an overall decline from 0.4364 to 0.3117; (2) the low-level units of urbanization level illustrated a strong convergence trend, and each unit possessed low eco-efficiency with weak spatial matching in general; (3) an ambiguous symbiosis exists between the center of gravity of movements of the two factors within each region; and (4) a global positive correlation was found between the urbanization level and eco-efficiency in Liaoning Province. The global Moran’s I index first increased and then decreased.